2022
DOI: 10.3390/ijerph19053124
|View full text |Cite
|
Sign up to set email alerts
|

Water, Sanitation and Hygiene in Schools in Low- and Middle-Income Countries: A Systematic Review and Implications for the COVID-19 Pandemic

Abstract: The global COVID-19 pandemic has revealed the extent to which schools are struggling with the provision of safe drinking water, sanitation and hygiene (WASH). To describe the WASH conditions in schools and discuss the implications for the safe reopening of schools during the ongoing COVID-19 pandemic, a systematic review of peer-reviewed literature on WASH in schools in low- and middle-income countries was performed. In April 2021, five databases, including MEDLINE (via PubMed), Web of Science, Scopus, AJOL, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 129 publications
(415 reference statements)
0
5
1
Order By: Relevance
“…While the JMP estimates that 5% of schools in Brazil have no sanitation service, which represents 2 million students without this resource in the school environment, our findings indicated that 22% of the Brazilian schools could be classified as with no sanitation service, ultimately impacting over 9 million of students. Nonetheless, the percentage of schools with improved sanitation facilities found in this study is higher than what was reported by Poague et al (2022) in LMICS (31%) and in Central America (64%, though this estimate was based on data from 412 schools included in only three studies).…”
Section: Discussioncontrasting
confidence: 85%
See 3 more Smart Citations
“…While the JMP estimates that 5% of schools in Brazil have no sanitation service, which represents 2 million students without this resource in the school environment, our findings indicated that 22% of the Brazilian schools could be classified as with no sanitation service, ultimately impacting over 9 million of students. Nonetheless, the percentage of schools with improved sanitation facilities found in this study is higher than what was reported by Poague et al (2022) in LMICS (31%) and in Central America (64%, though this estimate was based on data from 412 schools included in only three studies).…”
Section: Discussioncontrasting
confidence: 85%
“…As with WASH in schools monitoring, indicators vary between sources and countries, which hampers the comparison of WASH in schools across locations ( Chatterley et al, 2018 ). According to the systematic review on WASH in schools in LMICs conducted by Poague et al (2022) considering 18,465 schools described in 65 studies across 30 different countries, the water source in 6% of schools (n = 1118) was classified as “unknown” because the terms and indicators used in the studies did not fit the JMP classification. In Brazil, for instance, the standard when working with WASH is to use the definitions and indicators of the Plano Nacional de Saneamento Básico ( Brazil, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 11 Evidence in other countries 21 , 20 also supports these findings, especially in contexts where access to WASH has also been burdened during the syndemic. 48 For this reason, reusable products such as the menstrual cup may have facilitated menstrual management during lockdown. 49 Further research is needed to explore accessibility of menstrual products and menstrual poverty (including price regulations) among vulnerable populations, and particularly those who were highly burdened the economic impact of the syndemic or that were already in socioeconomic vulnerable contexts prior to the syndemic.…”
Section: Discussionmentioning
confidence: 99%